Young Driver Crashes with Cyclists: Identifying Training Opportunities. Issue 12 (December 2019) - Haworth, Narelle; Legge, Matthew; Twisk, Divera; Bonham, Jennifer; O'Hare, Tyler; Johnson, Marilyn
To understand where driver training should focus to contribute to improving the safety of cyclists, this study compared bicycle-motor-vehicle (BMV) crashes involving novice drivers (under 25 years) with those involving experienced drivers in the Australian states of Victoria, Queensland, and South Australia. Novice drivers were involved in only a small proportion of BMV crashes and were not over-represented on a per-license basis. For both driver groups, most crashes happened on lower speed roads, at intersections, and during the day. In contrast to expectations, the distribution of types of BMV crashes differed little between experienced and novice drivers. The absence of major differences between experienced and novice drivers may result from learning opportunities being too infrequent in low-volume cycling countries, but this hypothesis needs further testing. A comparison between Queensland and Victoria showed three situations with a higher proportion of young driver crashes: in the evening in both states, Right through-opposing directions (Victoria only), and From footway-maneuvering (Queensland only). These patterns are likely to be indicative of young driver experiences. When their time on the road increases, so does their exposure to risk and to challenging driving conditions (e.g., driving in darkness). On the other hand, these patterns may also point to effects of legislation on young driver crashes, for instance cycling on the sidewalk in Queensland. The results suggest that training for novice drivers needs to supplement a wider strategy to improve cyclist safety (including infrastructure and traffic management improvements) and that training needs to be tailored to state-specific conditions.